Neurophysiological functional imaging of the auditory system for evaluation of higher brain functions - Pratt, Hillel (Henry Stewart Talks, 2011)
Hearing is the primary modality of language and memory, Electrophysiological functional imaging is a direct manifestation of brain activity, Electrophysiological functional imaging has temporal resolution in the millisecond scale, The inverse problem of intracranial sources of scalp-recorded potentials is ill-posed, Estimate intracranial sources requires assumptions on head and nature of sources, Source current density estimation requires the least number of assumptions, Dyslexia, ADHD, Pseudobulbar Affect disorders, Quantitative measures of spatiotemporal distributions of activity show sensitivity at the population level and clinical promise at the individual patient level